Relative bioavailability of zinc in supplemental inorganic and organic sources for Nile tilapia Oreochromis niloticus fingerlings - Do Carmo E Sá, M. V.; Pezzato, Luiz Edivaldo [UNESP]; Barros, Margarida Maria [UNESP]; De Magalhães Padilha, P. [UNESP] (Hindawi, 2005)
A 90-day feeding experiment was conducted with sex reversed Nile tilapia (Oreochromis niloticus) fingerlings fed purified or practical diets supplemented with different zinc sources to evaluate fish growth performance and zinc and iron retention in fish bones, fillets, liver, skin and eyes. The relative bioavailability value (RBV) of zinc in the supplemental sources tested was also calculated. Fish were fed with isonitrogenous and isoenergetic purified or practical diets supplemented with 150 mg Zn kg -1, as zinc sulphate monohydrate (ZnSO 4), zinc oxide (ZnO) or zinc amino acid complex (Zn-AA). The feeding trial was conducted in 30, 50 L aquaria where four 0.66 ± 0.01 g (mean ± SD) fingerlings were initially stocked. No significant differences were observed for any growth performance variables (P > 0.05). In practical diets, only ZnSO 4 and ZnO presented bone zinc retention similar to that for the standard zinc source. Zinc concentration in the bone of fish fed practical diet supplemented with Zn-AA (171 ± 3.62 μg g -1) was significantly lower than that verified for the practical diets supplemented with the standard zinc source (200 ± 17.7 μg g -1) or with ZnSO 4 (204 ± 19.9 μg g -1). Assuming the concentration of zinc in bones as the response criterion, the supplemental zinc RBV from ZnSO 4 (105%) was higher than the RBV for Zn-AA (95.1%) or ZnO (94.9%). Iron concentration in the bones of animals fed the non-zinc-supplemented purified diet was significantly higher than that observed for purified diet supplemented with Zn-AA (P < 0,05). The results of the present work allowed us to conclude that ZnSO 4 in relation to ZnO or Zn-AA was the supplemental zinc source with higher zinc bioavailability to Nile tilapia. © 2005 Blackwell Publishing Ltd.
Keywords: Bioavailability; Chelate; Iron; Mineral nutrition; Tilapia; Zinc; Animalia; Oreochromis niloticus